Role of electron-phonon coupling in the thermal evolution of bulk Rashba-like spin-split lead halide perovskites exhibiting dual-band photoluminescence - Steele, Julian A. (2020)
The optoelectronic properties of lead halide perovskites strongly depend on their underlying crystal symmetries and dynamics, sometimes exhibiting a dual photoluminescence (PL) emission via Rashba-like effects. Here we exploit spin- and temperature-dependent PL to study single-crystal APbBr3 (A = Cs and methylammonium; CH3NH3) and evaluate the peak energy, intensity, and line width evolutions of their dual emission. Both perovskites exhibit temperature trends governed by two temperature regimes - above and below approximately 100 K - which impose different carrier scattering and radiative recombination dynamics. With increasing temperature, high-energy optical phonons activate near 100 K to drive energy splitting of the dual bands and induce line width broadening via electron-phonon coupling, with a stronger coupling constant inferred for carriers recombining by the spin-split indirect bands, compared to the direct ones. We find that the unusual thermal evolutions of all-inorganic and hybrid bulk lead bromide perovskites are comparable, suggesting A-site independence and the dominance of dynamic effects, and are best understood within a framework that accounts for Rashba-like effects.